Structure and regulation of the salivary gland secretion protein gene Sgs-1 of Drosophila melanogaster. - Roth, G.E.; Wattler, S.; Bornschein, H.; Lehmann, M.; Korge, G. (Genetics, 1999)
The Drosophila melanogaster gene Sgs-1 belongs to the secretion protein genes, which are coordinately expressed in salivary glands of third instar larvae. Earlier analysis had implied that Sgs-1 is located at the 25B2-3 puff. We cloned Sgs-1 from a YAC covering 25B2-3. Despite using a variety of vectors and Escherichia coli strains, subcloning from the YAC led to deletions within the Sgs-1 coding region. Analysis of clonable and unclonable sequences revealed that Sgs-1 mainly consists of 48-bp tandem repeats encoding a threonine-rich protein. The Sgs-1 inserts from single lambda clones are heterogeneous in length, indicating that repeats are eliminated. By analyzing the expression of Sgs-1/lacZ fusions in transgenic flies, cis-regulatory elements of Sgs-1 were mapped to lie within 1 kb upstream of the transcriptional start site. Band shift assays revealed binding sites for the transcription factor fork head (FKH) and the factor secretion enhancer binding protein 3 (SEBP3) at positions that are functionally relevant. FKH and SEBP3 have been shown previously to be involved in the regulation of Sgs-3 and Sgs-4. Comparison of the levels of steady state RNA and of the transcription rates for Sgs-1 and Sgs-1/lacZ reporter genes indicates that Sgs-1 RNA is 100-fold more stable than Sgs-1/lacZ RNA. This has implications for the model of how Sgs transcripts accumulate in late third instar larvae.